Peri-Urban Development as a Significant Rural Development Trend - Biegańska, Jadwiga; Środa-Murawska, Stefania; Kruzmetra, Zenija; Swiaczny, Frank (Quaestiones Geographicae, 2018)
The paper focuses on demographic and social changes caused by peri-urban development in rural areas in Latvia, Poland, and Germany after the system transformation began. The article analyses peri-urban development as a mostly rural phenomenon, and as a process of rural displacement. Rural development interacts with urban influences, changing the role and functions of rural areas. This is reflected by a departure from agricultural functions, more intensive construction activities and changes in land use. This also includes intensive socio-demographic and socio-cultural changes. Simultaneously there are significant population inflows, both urban and rural (from more peripheral rural areas), an increase in population density, changes of population structure etc. The paper shows that peri-urban development as a general rural trend began later in the countries of Eastern and Central Europe (after the transformation) than in Western Europe, but the processes and phenomena presently observed in Eastern and Western Europe are similar.